PEMODELAN CADANGAN BATUBARA BERDASARKAN PENENTUAN BATTERBLOCK DI SANGA DESA, MUSI BANYUASIN, SUMATERA SELATAN: MODELLING OF COAL RESERVES BASED ON BATTERBLOCK AT SANGA DESA, MUSI BANYUASIN, SOUTH SUMATERA - Permana, Darsa; Kurniawan, Dwiky Septa; Awad, Husni Muhammad; Pratama, Ravi Yuliansyah (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2025)
Reserves estimation are an effort to determine the economic value of minerals, as well as a basis for economic evaluation, whether the area under study is suitable or not suitable for mining. Reserves estimation are carried out at a coal mining company site in the Sanga Desa, Musi Banyuasin, Sumatera Selatan. Estimation are assisted by computer based program, namely Minescape 5.7 software. This research uses the block model method to determine potential coal areas. Based on this block model, a batter block is created in order to form a resgraph that can be used to determine the potential area to be mined by using Minescape 5.7, an estimate of coal reserves of 84,447,000 MT and overburden of 280,320,000 BCM obtained, so the stripping ratio is 3.3 with a pit area of 300.54 ha.